Feasibility of Arabic Textbooks Based on BSNP Criteria and Preparation Principles/Dirasat Judwa al-Kutub al-Dirasiyyah li al-Lughah al-‘Arabiyyah bina'an ‘ala Ma‘ayir BSNP wa Mabadi' I‘dad al-Kutub al-Dirasiyyah - Zakiyah, Fitri; Raudhatul Karimah; Mohamad Nor Amin Bin Samsun Baharun (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article investigated the feasibility of Arabic textbooks based on BSNP standards and the textbook preparation principles of Dr. Abdullah al-Gali and Dr. Abdul Hamid Abdullah. The background of this research stems from the importance of textbooks as the main medium in the learning process, directly influencing the quality of educational outcomes. A qualitative descriptive method was employed through literature review and document analysis. The primary data source was the Arabic textbook for grade X published by the Muhammadiyah Secondary and Primary Education Council, supported by relevant secondary documents. The findings showed that the textbook met the BSNP standards in terms of content, presentation, language, and graphic feasibility. It also aligned with the cultural, psychological, educational, and linguistic principles of textbook development. However, several issues were identified, such as punctuation errors and illustrations that were not fully appropriate. This research contributes to improving Arabic textbook quality and offers insights for future textbook development in accordance with national standards and pedagogical principles.